Development of Powtoon Application-Based Animated Videos on Hajj and Umrah Material at Middle School - Nanda, Islamia; Riawarda, Andi; Sunusi, Syamsu (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study intends to analyze the development stages of animated videos created using the Powtoon application for Hajj and Umrah material, as well as to evaluate the practicality and effectiveness of these animated videos. This study uses a development research approach with the ADDIE development model. The subjects of this study were Fiqh teachers and students of grade 8 at the Middle School, or Madrasah Tsanawiyah Suli, with a total of 22 students. The data collection techniques were interviews, observations, questionnaires, and documentation. This study employed a mixed-methods data analysis technique. The feasibility test results indicated that the material expert validator scored 81.81% in the